Theoretical and experimental investigation on the nonlinear vibration behavior of Z-shaped folded plates with inner resonance. (1st March 2019) - Guo, Xiangying; Zhang, Yang; Zhang, Wei; Sun, Lin
Highlights: The nonlinear dynamics of Z-shaped folded plates with inner resonance are investigated. The nonlinear dynamical behaviors of the Z-shaped folded plate are conducted by numerical simulation and compared with the results obtained by experiment. The middle plate yielded more complex vibration forms than the other two plates with increasing transverse excitations. Abstract: As one of the classical complex multibody structures, Z-shaped folded plates are widely applied in several engineering structures. In the present paper, the nonlinear vibration characteristics of a Z-shaped folded plate composed of three carbon-fiber composite plates were analyzed through theoretical and experimental investigation. The nonlinear dynamic model of the Z-shaped plate was developed based on the Hamilton principle, von Kármán equations, and the classical laminate plate theory, and the vibration mode shape functions of the system were calculated in ANSYS. Further, the Galerkin approach was employed to discretize the partial differential equations into a two-degrees-of-freedom nonlinear system, and the effects of transverse excitations on the nonlinear dynamic behavior of the Z-shaped folded plate were investigated through a comprehensive numerical simulation. Moreover, the obtained theoretical results were verified by experimental analysis. In addition, the vibration mode shapes of the Z-shaped folded plate were obtained by operational modal analysis (OMA). The modal parameters were first identified successfully using the PolyMAX method and then validated by modal assurance criterion (MAC). Finally, an excitation-measurement test was designed to measure the nonlinear vibration characteristics of the Z-shaped folded plate.